Birth weight of infants with spina bifida cystica. - Wald, N; Cuckle, H; Boreham, J; Althouse, R (1980)
The mean birth weight of 189 singleton infants with spina bifida cystica (including 21 with encephalocele) was statistically significantly less than the mean birth weight of 3816 singleton infants without neural tube defects, 0.20 kg less among male infants and 0.24 kg less among female infants. Most, if not all, of this difference in birth weight was due to the spina bifida infants being light for their gestational age. The difference could not be explained by differences in parity or social class.